ministerial decree 649/2016 Amending some provisions of the Executive Regulations of Law No. 144/2006 Regulating the Demolition of non-Dilapidated Buildings and Establishments, and the preservation of Archictectural Heritage - Egypt (2025)
Ministry of Housing, Utilities and Urban Communities Ministerial decree no. 649 of the year 2016 – Form of a Notice of intent to demolish sign قرارات وزارة الإسكان والمرافق والمجتمعات العمرانية قرار وزارى رقم 759 لسنة 2016 – نموذج لافتة للإعلان بالتقدم بترخيص هدم